2015
DOI: 10.1038/onc.2015.243
|View full text |Cite
|
Sign up to set email alerts
|

Minimal asbestos exposure in germline BAP1 heterozygous mice is associated with deregulated inflammatory response and increased risk of mesothelioma

Abstract: Germline BAP1 mutations predispose to several cancers, in particular malignant mesothelioma. Mesothelioma is an aggressive malignancy generally associated to professional exposure to asbestos. However, to date we found that none of the mesothelioma patients carrying germline BAP1 mutations were professionally exposed to asbestos. We hypothesized that germline BAP1 mutations might influence the asbestos-induced inflammatory response that is linked to asbestos carcinogenesis, thereby increasing the risk of devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(147 citation statements)
references
References 45 publications
11
136
0
Order By: Relevance
“…This hypothesis was supported by the findings in germline BAP1 heterozygous mice, where minimal exposure to carcinogenic fibers highly increased the risk of mesothelioma (15).…”
Section: Review Articlesupporting
confidence: 75%
See 1 more Smart Citation
“…This hypothesis was supported by the findings in germline BAP1 heterozygous mice, where minimal exposure to carcinogenic fibers highly increased the risk of mesothelioma (15).…”
Section: Review Articlesupporting
confidence: 75%
“…However, additional factors including SV40 infection (11)(12)(13), exposure to radiation, especially high doses radiotherapy of lymphoma and other chest malignancies (1), may also cause mesothelioma, possibly in concert with asbestos (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature, however, supports the hypothesis that monoallelic losses of these genes are of biological relevance: (i) In mice, monoallelic losses of Bap1 alter asbestos-induced peritoneal inflammatory response (42) and induce ccRCC in the presence of a coexisting Vhl deficiency (43). (ii) In chronic lymphocytic leukemia, SETD2 alterations are very often monoallelic, and epigenetic inactivation of the wild-type allele is absent.…”
Section: Discussionmentioning
confidence: 88%
“…Subsequently, we discovered that germline BAP1 truncating mutations caused a very high incidence of mesothelioma in some US families in the absence of occupational asbestos exposure (28). Moreover, using a BAP1 +/− mouse model, we demonstrated that mice carrying germline BAP1 mutations develop mesothelioma following exposure to very low doses of asbestos that rarely cause mesotheliomas in wild-type mice (29). Our data, confirmed and expanded by others, showed that germline BAP1 mutations are also associated with uveal melanoma (28) and other malignancies (30-37).…”
Section: Brca-associated Protein 1 (Bap1) and Mesotheliomamentioning
confidence: 94%